Aplikasi Pemupukan Pada System of Rice Intensification Terhadap Pertumbuhan dan Hasil Padi Saat Musim Kemarau - Ardiansyah; Yugi R. Ahadiyat (Jurnal Penelitian Pertanian Terapan, 2020)
The regular application of synthetic fertilizers in every rice planting season has the potency to be a pollutant on the environment. Therefore, it is necessary to apply a rice cultivation system that is more environmentally friendly by utilizing organic fertilizers and biological agents as substitutes for synthetic fertilizers with the System of Rice Intensification (SRI) method. The objective of this study was to determine the growth and yield of rice by the SRI method during the dry season with the application of organic fertilizers and biofertilizers. The study was conducted in Banjaranyar Village, Sokaraja District, Banyumas Regency. The study used a divided plot design with main plots of rice varieties namely Situ Bagendit and IR 64, and types of fertilizers, namely NPK fertilizer (urea, SP36, KCl), organic fertilizers, and biofertilizer as subplots with three replications. The variables observed included plant height, number of productive tillers, leaf area, shoot dry weight, panicle length, number of filled grains per hill, grain weight per hill, effective grain weight per plot, 1000 grains weight, grain weight per hectare, and harvest index. The data were analyzed by using the F test and if it showed a significant difference, then continued with the LSD test with a confidence level of 95% to determine the effect of each treatment tested on the observed variables. The results showed that the Situ Bagendit variety gained a higher number of productive tillers and larger leaf area than the IR 64 variety, but both varieties gave equivalent yields in yield components ranged 1.5-1.6 t/ha. Organic fertilizers and biofertilizers were able to reduce the use of synthetic fertilizers due to provide equivalent yield in both varieties.